(untitled) (The Pakistan Development Review, 1986)
Taxation of the agricultural sector is a major instrument for mobilization of the surplus to finance development projects within the agricultural sector and/or the rest of the economy. For many years, the need for a heavier taxation of agricultural land has formed part of the conventional wisdom regarding the ways of extracting agricultural surplus and increasing the tempo of agricultural development in poor countries. Land taxes have both equity and efficiency properties that gladden the hearts of both economists and vocal politicians belonging to urban areas. Taxes on land promote efficiency in the allocation of scarce resources by creating incentives for farmers to increase their effort and reduce their consumption, thus expanding the amount of agricultural produce available to the non-agricultural sectors of the economy. A tax on land has an important redistributive function because its incidence falls squarely on the landlord and is shifted neither forward to consumers nor backwards to suppliers of agricultural inputs; nor does it introduce distortions in the allocation of productive resources.